The Significance Of Narrative To Interpret â€˜Sherlock Holmesâ€™ Characterin Museums - Hanny Wijaya (PANGGUNG, 2015)
This research focuses on the study of Sherlock Holmes character that has been a famous detective icon in the world, where this character then become the main theme interpreted by the museum.Â  The method employed by the museum to â€œnarrateâ€ that particular character is very significant to determine the objective and background for the museum as the exhibition organizer. Narration holds a crucial role to â€œguideâ€ the understanding of the audiences to a character, or sometimes can make â€œconfusionâ€ to the audience when differentiate whether the character is fiction or non-fiction. By comparing the narration on the permanent displays of Museum of Sherlock Holmes to temporary exhibition display in Museum of London with Sherlock Holmes theme, it can be seen the significance of the relation between narration and interpretation of a character that also determine the message of that museum.Keywords: Narration, interpretation, Sherlock Holmes, museum, exhibition